STRATEGI KOMUNIKASI PERSUASIF PERSONAL SELLING DALAM MENINGKATKAN NASABAH PADA PRODUK ASURANSI UMUM DI PT. JASARAHARJA PUTERA CABANG PEKANBARU - Yanie Pratiwi Firdaus; Evawani Elysa Lubis (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
Insurance is a product or service that is visible and there is no clarity of goods, therefore, the general public does not trust the insurance with a variety of things, such as a lack of confidence in the insurance, especially the old and procedures that are considered difficult to process a claim if a loss, and the rate high. PT. Jasaraharja Putera Branch Pekanbaru selling face to face (personal selling) with the aim to explain about the products offered. This study aims to determine the approach to personal selling persuasive communication strategy to improve customer on general insurance products of PT. Jasaraharja Putera, and knowing the techniques of persuasive communication in improving customers' personal selling on general insurance products of PT. Jasaraharja Putera Branch Pekanbaru. This research was conducted at PT. Jasaraharja Putera Branch Pekanbaru Jl. Jenderal Sudirman No. 258 Pekanbaru, Riau. This study uses qualitative research method with descriptive approach to data collection techniques are observation, interview (interview) and documentation. Informants in this study as many as 14 people are marketers and customers in PT. Jasaraharja Putera Branch Pekanbaru. Data were analyzed using analysis model of Miles and Huberman interactive data by collecting data obtained are then processed to be reduced, served to produce a general conclusion. The results of this study indicate that PT. Jasaraharja Putera Branch Pekanbaru in improving the customer on general insurance products using a strategy of persuasive communication by way of direct sales (personal selling) where marketers approach the strategy of psychodynamics is a strategy that focuses on emotional factors and cognitive factors with the message of persuasion, persuasion sosialkultural is changing customer behavior influenced by outside individuals or from consensus (a big boost), and the strategy of the meaning constraction is a persuasion by giving knowledge to customers through mass media. The techniques of persuasive communication by way of personal selling is done marketers to improve customer, using the technique of the yes-response technique is a technique in which marketers persuade its customers to respond to the statement that the prospective customer to answer